Spiritual leadership in action : the CEL story, achieving extraordinary results through ordinary people - Fry, Louis W.; Altman, Yochanan (Advances in workplace spirituality., 2013)
Spiritual Leadership in Action: The CEL Story is designed for thoughtful leaders working in the complexity and messiness of their daily organizational lives. It is a book first and foremost about people, about the ways they find purpose, creativity and meaning in their professional work; how they thrive in community and fulfill their deep desire to be of service to others against seemingly impossible odds and limitations. A study of how full human potential and creativity is released, how the spirit within, and without, can be experienced and manifested. It is also story of ordinary people achieving extraordinary results, individually and collectively; of people becoming more than they thought was possible; and having fun along the way. This is a practical book with reflections, legacy and "lessons learnt" to support and guide busy leaders who are looking for wisdom and to learn from the experiences and mistakes of others. Spiritual Leadership in Action: The CEL Story is the result of serious and rigorous academic research. It is a case study containing features, dilemmas and opportunities facing all leaders today. A leadership narrative of a professional community who learned to live and work together with respect and harmony. It is also the story of a CEO leader and the integration of her spiritual yearning and fulfillment manifested through her professional vocation and calling. In particular it explores how: * To create effective collaborative partnerships * To deliver outstanding value for money on limited resources in complex contexts * To develop excellent commercial practices within a public sector organization * To nurture the spirit, high energy and performance of everyone involved to ensure outstanding success on the triple bottom line This book challenges the reader to be bold, creative, reflective, trusting, even more allowing of their own spirit and leadership path, and to rise to even greater achievements; but most of all to fulfill their own deepest yearnings and potential and to become the very best of what they are meant to be, both as a leader and as a human being. An important feature in this book is that spirituality and religion are distinct, and that organizational spiritual leadership can be inclusive or exclusive of religious theory and practice. The Centre for Excellence in Leadership (CEL) serves as a role model for maximizing the triple bottom line through both personal and organizational spiritual leadership. CEL is a stellar example of an organization that embraced organizational spiritual leadership, the values of altruistic love, employee well-being, and sustainability while maintaining high levels of financial performance. Spiritual Leadership in Action: The CEL Story chronicles how, as CEO, Lynne Sedgmore led CEL through its spiritual journey, including several "Dark Nights of the Soul," to a place of pre-eminence in the United Kingdom's Learning and Skills sector.